Comparable Genital Tract Infection, Pathology, and Immunity in Rhesus Macaques Inoculated with Wild-Type or Plasmid-Deficient Chlamydia trachomatis Serovar D - Qu, Yanyan (Infect Immun, 2015)
Rhesus macaques were studied to directly address the potential for plasmid-deficient Chlamydia trachomatis to serve as a live attenuated vaccine in the genital tract. Five repeated cervical inoculations of rhesus macaques with wild-type serovar D strain D/UW-3/Cx or a plasmid-deficient derivative of this strain, CTD153, resulted in infections with similar kinetics and induced comparable levels of protective immunity. After all animals received five challenges with D/UW-3/Cx, levels of inflammation observed grossly and histologically were similar between the groups. Animals in both groups developed evidence of oviduct dilatation; however, reduced oviduct dilatation was observed for “controllers,” i.e., animals without detectable chlamydial DNA in the fimbriae at weeks 5 and 12. Grouping animals into “ascenders” and “controllers” revealed that elevated early T cell responses were associated with protection, whereas higher antibody responses were associated with ascension. Protected animals shared common major histocompatibility complex (MHC) alleles. Overall, genetic differences of individual animals, rather than the presence or absence of the chlamydial plasmid in the primary infecting strain, appeared to play a role in determining the outcome of infection.